A subtractive modelling approach for predicting the radiation of a cylindrical shell in a waveguide - Dumortier Florent; Kha Jamie; Karimi Mahmoud; Meyer Valentin; Maxit Laurent (Acta Acustica, 2025)
Modeling the sound radiated from underwater structures immersed in various environments is necessary in ocean acoustics and naval engineering. Typically, an underwater vibroacoustic system is composed of an elastic cylindrical shell that is radiated into an unbounded fluid domain. However, in contrast to deep oceans, for a shallow water environment, the influence of the sea surface and seabed can no longer by ignored. The significant fluid-structure interaction arising from the coupling at the boundary of the structure and surrounding fluid complicates the prediction of vibroacoustic behaviour. A sub-structuring technique based on the condensed transfer function (CTF) approach and reverse condensed transfer function (rCTF) approach has been proposed recently to tackle complex vibroacoustic problems by coupling/decoupling the necessary subsystems. Its potential is demonstrated in the present study through a two-dimensional case study to predict the sound radiation from an elastic structure of a cylindrical shell excited by a harmonic line force and immersed in a fluid domain of a perfect underwater acoustic waveguide, that is composed of an upper free surface and a lower rigid floor. The targeted model is obtained from a perfect underwater waveguide in which a water disk is subtracted from, and an excited shell is added in place of the water disk. The predictions of the proposed CTF-rCTF process are verified against analytical solutions for two different partitions of the global system and two types of condensation functions.